Between public health and commercial pressure: health communication and media oversight in Indonesia local radio - Sufyan Abdurrahman, Muhammad; Putra, Dedi Kurnia Syah; Widyaningrum, Septiana Yustika; Ali, Aditya; Parsono, Slamet (Frontiers in Communication, 2025)
This study investigates the proliferation of herbal medicine advertising on local radio stations in West Java, Indonesia, with attention to regulatory gaps, media ethics, and public health risks. Using a qualitative case study approach, data were collected between late 2023 and 2024 through interviews, observation, and document analysis. Informants included radio personnel, officials from the West Java Regional Food and Drug Supervisory Agency (BBPOM), and relevant industry stakeholders. Data were gathered between late 2023 and 2024, a period that witnessed significant shifts in media financing and advertising practices. Findings show that economic pressures during and after the COVID-19 pandemic led stations to rely heavily on herbal advertisers—some of whom acquired influence over content or ownership. This dependency compromised editorial autonomy and blurred regulatory compliance, with many ads promoting unverified health claims, testimonials, and products beyond approved uses. The study highlights fragmented enforcement among BBPOM, the National Agency of Drug and Food Control (BPOM), the Regional Broadcasting Commission (KPID), and the Ministry of Communication and Informatics (Kominfo), enabling misleading content to persist. Interpreted through the lens of political economy and neoliberal governance, the findings reveal how market survivalism and cultural trust in “natural” remedies reshape media practices. This research contributes to understanding how commercial pressures and institutional disconnection endanger ethical health communication in Indonesia’s evolving broadcast landscape.